ANALYSIS OF THE INFLUENCE OF INFLATION, EXCHANGE RATE, AND POPULATION ON INDONESIA'S ECONOMIC GROWTH 1993–2023: VECM APPROACH - Aqil Widyantoro, Ahmad; Dwi Atmanti, Hastarini (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the influence of inflation, exchange rate, and population on Indonesia’s economic growth from 1993 to 2023 using the Vector Error Correction Model (VECM) approach. The research utilizes secondary data obtained from the Central Statistics Agency (BPS) and the World Bank. The stationarity test shows that most variables become stationary at the first difference. Johansen cointegration test results indicate a long-term equilibrium relationship among the variables. In the short run, VECM estimation results show that only the population variable is significantly affected by changes in other variables, while inflation and exchange rate do not show significant short-term impacts. The Impulse Response Function (IRF) and Variance Decomposition analysis confirm that population has a more dominant and persistent effect on economic growth compared to inflation and exchange rate, both of which exhibit relatively weak influence. These findings highlight the strategic role of demographic dynamics in shaping macroeconomic performance. Therefore, improving population quality and managing demographic trends should be prioritized in national development planning to support inclusive and sustainable economic growth in Indonesia.